Preparation and Characterization of a three-component hydrogel composite and study of kinetic and thermodynamic applications of adsorption of some positive and negative dyes from their aqueous solutions. Issue 5 (November 2020) - Adheem, Hamzah M.; Jasim, Layth S.
Abstract: The composite hydrogels (AAC-co-AM)-g-MCC based on microcrystalline cellulose (MCC) and poly(acrylic acid-co-acrylamide) were synthesized by free radical polymerization in an aqueous suspension of (MCC) which use as initiator for the reaction, the structure and surfaces of hydrogels was characterized and analyzed with (FTIR), Xray diffraction spectroscopy (XRD), (FE-SEM) and thermogravimetric analysis (TGA). The adsorption mechanisms understand the dyes on surface of composite by thermodynamic Study of adsorption process Which include measuring the Enthalpy and Entropy and Gibbs energy, In addition, the dyes adsorption process accorded with pseudo-second-order rate equation, It also showed that adsorption isotherm of the composite Hydrogel is govern by Langmuir and Friendlish equations, The adsorption of dyes is a Physical adsorption, Based on structure analysis and adsorption kinetics of composite, the adsorption process was controlled by the ion-exchange mechanism.